2006
DOI: 10.3354/meps322213
|View full text |Cite
|
Sign up to set email alerts
|

Filter feeding in the burrowing amphipod Corophium volutator

Abstract: The present study shows that when suspended phytoplankton cells are present at sufficiently high concentrations the tube-dwelling marine amphipod Corophium volutator (Pallas) filter feeds, but when the phytoplankton biomass reaches a certain low level, both laboratory and field video observations support the hypothesis that C. volutator can switch to surface deposit feeding. Feeding behaviour and quantification of water processing were studied in individuals transferred to glass tubes. Simultaneous clearance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The filter is made up of fine bristles (setules) on the setae, and the distance between the bristles is ∼7 µm. The filter basket may efficiently retain particles with diameters > 7 µm, which has been supported by the experimentally measured particle retention efficiency (Møller & Riisgård 2006). Riisgård (2007a) studied the integrated function of the setal filter-basket and the pleopodal pump in C. volutator.…”
Section: Amphipodsmentioning
confidence: 88%
“…The filter is made up of fine bristles (setules) on the setae, and the distance between the bristles is ∼7 µm. The filter basket may efficiently retain particles with diameters > 7 µm, which has been supported by the experimentally measured particle retention efficiency (Møller & Riisgård 2006). Riisgård (2007a) studied the integrated function of the setal filter-basket and the pleopodal pump in C. volutator.…”
Section: Amphipodsmentioning
confidence: 88%
“…, 2008). Temperature, which can regulate the feeding rate of aquatic invertebrates (Hymel & Plante, 2000; Moller & Riisgard, 2006), may also regulate the metabolic rate of denitrifying bacteria in the gut directly. In other words, seasonal changes in temperature may influence the degree of gut filling (and hence bacterial biomass) and the rate of bacterial N 2 O production in the gut, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In aquatic sediments, seasonal variability in temperature and NO À 3 availability regulates denitrification rate and the N 2 O ⁄ N 2 production ratio (Pina-Ochoa & Alvarez-Cobelas, 2006;Silvennoinen et al, 2008). Temperature, which can regulate the feeding rate of aquatic invertebrates (Hymel & Plante, 2000;Moller & Riisgard, 2006), may also regulate the metabolic rate of denitrifying bacteria in the gut directly. In other words, seasonal changes in temperature may influence the degree of gut filling (and hence bacterial biomass) and the rate of bacterial N 2 O production in the gut, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…microalgae) was provided using peristaltic pumps with a pure culture of the diatom Thalassiosira weissflogii. The cell concentration was determined using a Malassez cell counting chamber and the relationship between Chl a (µg.L -1 ) and cell concentration (C c 10 3 cell.mL -1 ) was Chl a = 2.7 x Cc (Møller and Riisgård, 2006). To mimic an increasing range of particulate inorganic matter (hereafter PIM), silt (Kaolinite BS1, AGS Montguyon, France) was added to the diet.…”
Section: Determination Of Feeding Activitymentioning
confidence: 99%
“…20 µm) corresponding to the particles efficiently retained by Haploops antennae. For the amphipod Corophium volutator, Møller and Riisgård (2006) showed that the distance between two brittles on the gnathopods (filter organs) corresponds to the particle diameter retained with 100% efficiency (i.e. 6-7 µm).…”
Section: Effects Of Environmental Parameters On Feeding Activity In Hmentioning
confidence: 99%